Evaluation of the Quality of Teaching in Neurology Ward Kerman University of Medical Sciences Iran from the Point of View of Medical Students - Farhad Iranmanesh; Akbar Hamzei Moghaddam; Mohammad Ali Shafa (Kerman University of Medical Sciences, 2013)
Background & Objective: In educational systems evaluation is considered as one of the key elements The evaluation of university students on the educational processes is of specific value There has been no study on the evaluation of the Neurology Department Kerman University of Medical Sciences Iran through carrying out a poll Therefore we intended to improve the quality of education in the department through evaluation Methods: From among the medical students admitted in 2007 in Kerman University of Medical Sciences Iran 67 students participated in the present study The questionnaire used was prepared according to reliable sources and the professors points of view and considered validity and reliability The questionnaires data was entered into SPSS and it was statistically analyzed through descriptive and analytical statistical methods Results: 63 students (94%) rated the methodology of the professors of the ward and 62 students (925%) rated the methodology of the professors of theoretical courses a moderate or high score 65 students (97%) evaluation of good behavior of professors with students was moderate or high In terms of efficiency 35 students (522%) rated morning reports 28 students (417%) rated weekly conferences and 18 students (268%) rated journals a moderate to high score Conclusion: According to the medical students opinion the neurology department has a good position in general standards of medical education ethics and regulation However it has to reconsider some parts of educational procedures such as conferences and journal clubs which are held in collaboration with the residents